2015
DOI: 10.1021/acs.nanolett.5b03483
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Shape Memory Effect in Bent Cu–Al–Ni Nanopillars: When Twin Boundaries Become Stacking Faults

Abstract: Bent Cu–Al–Ni nanopillars (diameters 90–750 nm) show a shape memory effect, SME, for diameters D > 300 nm. The SME and the associated twinning are located in a small deformed section of the nanopillar. Thick nanopillars (D > 300 nm) transform to austenite under heating, including the deformed region. Thin nanopillars (D < 130 nm) do not twin but generate highly disordered sequences of stacking faults in the deformed region. No SME occurs and heating converts only the undeformed regions into austenite. The defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Their domain switching and domain wall (or twin boundary) motion dominate these effects. For example, Cu-Al-Ni nanopillars show a strong shape memory recoverability through twinning and de-twinning mechanisms, while this effect is destroyed by high densities of stacking faults in small size nanopillars [1]. In Ti-Ni-based shape memory alloys, the motion of twin boundary could improve fatigue resistance when the temperature is below the martensitic transition temperature [2].…”
Section: Introductionmentioning
confidence: 99%
“…Their domain switching and domain wall (or twin boundary) motion dominate these effects. For example, Cu-Al-Ni nanopillars show a strong shape memory recoverability through twinning and de-twinning mechanisms, while this effect is destroyed by high densities of stacking faults in small size nanopillars [1]. In Ti-Ni-based shape memory alloys, the motion of twin boundary could improve fatigue resistance when the temperature is below the martensitic transition temperature [2].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the damage tolerance of these nanocomponents, it is desirable to achieve fully reversible deformation exceeding the elastic strain limit, which is known as pseudoelasticity (see Supporting Information Figure S1). While shape memory effects originating from stress-induced martensitic phase transformation can exhibit a certain extent of pseudoelasticity, , this mechanism is no longer applicable to refined sample sizes of sub-100 nm. Furthermore, the twinning/surface-mediated pseudoelastic behaviors of nanocrystals ,,, , are either limited to specific crystallographic orientations or lack controllability, making it challenging to control the pseudoelastic strain for various applications.…”
mentioning
confidence: 99%
“…Several studies have indicated that the superelastic response of SMA pillars has a strong size-dependence. Ozdemir et al reported that the superelasticity of [110] Ni 54 Fe 19 Ga 27 shape memory alloy single crystal pillars start to diminish once the diameter of pillars D < ∼1 μm. It was suggested that the irreversible plastic deformation observed is due to the formation of stabilized martensites, even though there was no direct experimental evidence.…”
mentioning
confidence: 99%